Erratum: Chauveau, O., Pastori, T., Souza-Chies, T.T. & Eggers, L. (2014) Overlooked diversity in Brazilian Cypella (Iridaceae, Iridoideae): four new taxa from the Río de la Plata grasslands. Phytotaxa 174 (1): 25–42. - Chauveau, Olivier; Pastori, Tamara; Souza-Chies, Tatiana T.; Eggers, Lilian (Phytotaxa, 2020)
We have noticed an inadvertent error in our article entitled “Overlooked diversity in Brazilian Cypella (Iridaceae: Iridoideae): four new taxa from the Río de la Plata grasslands” (Phytotaxa 174 (1): 25–42).